Analysis of Profitability Ratios on Market Perception of Pharmaceutical Sub-Sector Companies (2017-2022) - Siva Silvia; Firda Eka Riyanti; Eriani Herawati; Hilda Nurizka Permata Sari; Dito Rinaldo (Jurnal Ecoment Global, 2023)
Objective :This study was conducted to determine the difference between NPM, ROA and Stock Price before and after the pandemic, as well as to find out how the influence of NPM and ROA on market perception in pharmaceutical sub-sector companies for the period 2017 - 2022.   Design/Methods/Approach : The data collection method uses secondary data from the company's financial statements. Purposive sampling was used for sampling in the study which made eight companies as objects. T-test and linear regression analysis are the techniques for analyzing this data.   Findings  :The t-test research results show that there is no difference between NPM, ROA, and Market Perception before and after the pandemic. This can be caused by erratic market behavior. The T test and F test show that NPM and ROA partially and simultaneously have no significant effect on market perception. Originality/Value: Market perception in pharmaceutical sub-sector companies for the period 2017 - 2022. The T test and F test With SPSS Practical/Policy implication : In this case, market perception is not only influenced by financial performance, especially profitability, but is influenced by many other factors